A Review on Major Rust Resistance Gene and Amino Acid Changes on Wheat (Triticum aestivum L) - Bikas Basnet; Philomin Juliana; Keshav Bhattarai; Umisha Upreti (Advances in Agriculture)
Wheat ranks first in the production and productivity of staple cereal crops in the world. Several diseases, including Stripe (Puccinia striiformis f. Sp. tritici), Black (Puccinia graminis f. Sp. tritici), and Brown (Puccinia recondita), have a major negative impact on wheat output, with 20 to 80% loss annually. Growing rust-resistant varieties is the most durable, cost-effective, and environmentally friendly way to combat rust pathogens. In the present review, we provide updated information on all black stem rust, yellow leaf rust, and brown leaf rust resistance genes including chromosomal position, those derived from different sources, nature of resistance type, and amino acid changes done by this gene against rust pathogen. This study summarized the 68 black stem rust, 101 leaf rust, and 108 stripe rust resistance genes from diverse cultivars of wheat and wheat primary and secondary gene pools. This review will be valuable to wheat breeders in cloning rust-resistant genes and developing leaf as well as stem rust-resistant wheat cultivars using gene pyramiding as well as frequency multiplication through introgression of the gene of interest for disease-free, sustainable grain production of wheat. The success of pyramiding genes from other sources to bread wheat depends on the nature of germplasm, the gap between flanking marker and targeted genes, the selection of genotypes in each generation, large number of gentoyes large genotype-environment interaction, etc., which is the future area of study.